2023
DOI: 10.1021/acsomega.2c07993
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Coumarin Triazoles as Dual Inhibitors of Cholinesterases and β-Secretase

Abstract: Coumarin is a naturally occurring bioactive pharmacophore with wide occurrence among central nervous system (CNS)-active small molecules. 8-Acetylcoumarin, one of the natural coumarins, is a mild inhibitor of cholinesterases and β-secretase, which are vital targets of Alzheimer’s disease. Herein, we synthesized a series of coumarin–triazole hybrids as potential multitargeted drug ligands (MTDLs) with better activity profiles. The coumarin–triazole hybrids occupy the cholinesterase active site gorge from the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
(67 reference statements)
1
9
0
Order By: Relevance
“…A series of coumarin−triazole hybrid syntheses conducted by Sharma and Bharate (2023) relied on the propargylation of 8-acetyl-coumarin 193 with propargyl bromide to give compound 194 ( Scheme 44 ) [ 111 ]. The click reaction of the propargyl 194 with benzyl bromide 195 in the presence of sodium azide yielded the corresponding coumarin−triazole hybrids 196a – d in medium yields.…”
Section: Synthesis Of Coumarin Coumarin–chalcone Hybrids and Coumarin...mentioning
confidence: 99%
See 3 more Smart Citations
“…A series of coumarin−triazole hybrid syntheses conducted by Sharma and Bharate (2023) relied on the propargylation of 8-acetyl-coumarin 193 with propargyl bromide to give compound 194 ( Scheme 44 ) [ 111 ]. The click reaction of the propargyl 194 with benzyl bromide 195 in the presence of sodium azide yielded the corresponding coumarin−triazole hybrids 196a – d in medium yields.…”
Section: Synthesis Of Coumarin Coumarin–chalcone Hybrids and Coumarin...mentioning
confidence: 99%
“…The coumarin–triazole hybrids developed by Sharma and Bharate (2023) [ 111 ] were screened for their inhibition of ChEs and BACE-1. The most active compound, 196b ( Scheme 44 , Figure 9 ), inhibited acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and β-secretase-1 (BACE-1) with IC 50 values of 2.57, 3.26, and 10.65 μM, respectively.…”
Section: Bioactivity Of Coumarins Coumarin–chalcones and Coumarin–tri...mentioning
confidence: 99%
See 2 more Smart Citations
“…Ankita et al [40] reported a number of coumarin‐triazole hybrids ( 92 – 95 ) (Figure 22) in order to design new multitargeted therapeutic ligands with enhanced activity profiles. The coumarin‐triazole hybrids reside a gorge between the catalytic anionic site and the periphery of the cholinesterase active sites.…”
Section: Introductionmentioning
confidence: 99%